Description, molecular characterisation, diagnostics and life cycle of Plasmodium elongatum (lineage pERIRUB01), the virulent avian malaria parasite. Issue 11 (October 2016) - Palinauskas, Vaidas; Žiegytė, Rita; Iezhova, Tatjana A.; Ilgūnas, Mikas; Bernotienė, Rasa; Valkiūnas, Gediminas
Graphical abstract: Highlights: Plasmodium elongatum (pERIRUB01) is a highly virulent malaria parasite. Massive infestation of bone marrow cells causes death of infected canaries. The syncytia in blood circulation can serve as a template for PCR amplification. Exoerythrocytic stages of pERIRUB01 develop in the bone marrow, spleen and liver. Abstract: Plasmodium elongatum causes severe avian malaria and is distributed worldwide. This parasite is of particular importance due to its ability to develop and cause lethal malaria not only in natural hosts, but also in non-adapted endemic birds such as the brown kiwi and different species of penguins. Information on vectors of this infection is available but is contradictory. PCR-based analysis indicated the possible existence of a cluster of closely related P. elongatum lineages which might differ in their ability to develop in certain mosquitoes and birds. This experimental study provides information about molecular and morphological characterisation of a virulent P. elongatum strain (lineage pERIRUB01) isolated from a naturally infected European robin, Erithacus rubecula . Phylogenetic analysis based on partial cytochrome b gene sequences showed that this parasite lineage is closely related to P. elongatum (lineage pGRW6). Blood stages of both parasite lineages are indistinguishable, indicating that they belong to the same species. Both pathogens develop in experimentally infected canaries, Serinus canaria, causing death of the hosts. In both these lineages, trophozoites and erythrocytic meronts develop in polychromatic erythrocytes and erythroblasts, gametocytes parasitize mature erythrocytes, exoerythrocytic stages develop in cells of the erythrocytic series in bone marrow and are occasionally reported in spleen and liver. Massive infestation of bone marrow cells is the main reason for bird mortality. We report here on syncytium-like remnants of tissue meronts, which slip out of the bone marrow into the peripheral circulation, providing evidence that the syncytia can be a template for PCR amplification. This finding contributes to better understanding positive PCR amplifications in birds when parasitemia is invisible and improved diagnostics of abortive haemosporidian infections. Sporogony of P. elongatum (pERIRUB01) completes the cycle and sporozoites develop in widespread Culex quinquefasciatus and Culex pipiens pipiens form molestus mosquitoes. This experimental study provides information on virulence and within species lineage diversity in a single pathogenic species of haemosporidian parasite.